PENGARUH PENAMBAHAN BAGIAN DAN LEVEL JANTUNG PISANG TERHADAP KUALITAS FISIK SOSIS DAGING SAPI - Abdul Hakim Fattah; Muhammad Nur Hidayat (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. This study aims to determine the effect and level section of banana and interaction both on the physical quality of beef sausage. Research using a completely randomized design factorial pattern 3 x 3 each with three replications. Factor is 3 parts of banana (Interior, Exterior and Mixed), Factor B is the level of use (0%, 15 and 30%). Parameters measured were cooking shrinkage, breaking power, power iris and pH. The study concluded that: 1) Addition of banana intact produce sausages that have tenderness (power break) and iris power higher than the sausage with the addition of banana inside and the outside, but did not make a difference in the shrinkage cookware and pH sausage. 2) The higher levels of addition of the higher shrinkage cookware, tenderness and a social and iris power, no difference in the effect of banana on the pH level of the sausage. 3) The interaction factor and level section of banana showed no difference in response to shrinkage cookware, powerbreaking, power and pH sausage slices.